Analysis of Economic Growth and Carbon Emissions in Indonesia - Kinski, Natasya; Hidayat, Paidi; Suhaimi, Syech (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The increase in greenhouse gas emissions particularly carbon dioxide, which remains a major global energy concern, continued to rise by 0.9 percent in 2022 following the COVID-19 pandemic. Indonesia ranks sixth globally as one of the largest emitters, with coal-based industries contributing the majority of its emissions. This study employs a quantitative approach using the variables of economic growth, energy consumption, deforestation, and foreign direct investment (FDI) over the period 1990–2022. The data were obtained from the World Bank and various international and Indonesian academic publications. The results show that economic growth significantly increases carbon emissions, whereas deforestation and FDI reduce emissions; energy consumption exhibits no significant effect. Overall, the findings indicate that rising carbon emissions in Indonesia are driven by environmentally unsustainable economic expansion, consistent with the Environmental Kuznets Curve (EKC) hypothesis. This is further supported by the impulse response function and variance decomposition analyses, which highlight the positive association between economic growth and carbon emissions. Meanwhile, deforestation and FDI do not contribute to higher emissions, and the transition toward more sustainable energy consumption in Indonesia results in an insignificant impact on emission growth